Measuring Social Capital in Adult Education Projects - Jeff Zacharakis (Adult Education Research Conference, 2006)
This theoretical research analyzes the measurement of social capital in adult education and community development projects that seek to strengthen democratic processes and develop local leadership. It analyzes two different methodologies—in depth interviews and Web-based questionnaires—used to measure social capital.
Keywords: Community development; leadership development; and social capital